Multi-dimensional Learning in the 5th Grade General Music Classroom: Supplemental Files - Hoefer, Katherine Anne (My University, 2018)
My lesson plan shown in my video teaching demonstration will show 5th graders performing a traditional song from the Apache tribe by singing, playing xylophones and other non-pitched percussion instruments, and playing a passing game. These students will accompany their voices by playing an ostinato pattern on the xylophone. I have developed as a teacher through the Masters’ Program because I have learned new ways of teaching, especially when it comes to exposure to Orff and Kodaly methodologies, and improvisation within the classroom. I am now more comfortable incorporating improvisation, as well as music from many other cultures into my lessons, and my students are growing as musicians and as people due to it.
Keywords: Music Education; Elementary Music; Multi-Dimensional; General Music; Orff